2007
DOI: 10.1111/j.1365-2133.2007.07801.x
|View full text |Cite
|
Sign up to set email alerts
|

Class I and class II major histocompatibility complex genes in Mexican patients with actinic prurigo

Abstract: 4 Dalle S, Balme B, Sebban C et al. Schnitzler syndrome associated with systemic marginal zone B-cell lymphoma. Br J Dermatol 2006; 155:827-9. 5 Baty V, Hoen B, Hudziak H et al. Schnitzler's syndrome: two case reports and review of the literature. Mayo Clin Proc 1995; 70:570-2. 6 Pascual-López M, Hernández-Núñez A, Sánchez-Pérez J et al. Schnitzler's syndrome with monoclonal IgG kappa gammopathy: good response to cyclosporin. J Eur Acad Dermatol Venereol 2002; 16:267-70. 7 Modiano P, Barbaud A, Laveine E et al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
1
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 9 publications
1
8
1
2
Order By: Relevance
“…La distribución geográfica de este alelo puede explicar por qué el prurigo actínico es más común en algunos lugares de Norteamérica, Centroamérica y Suramérica. Aunque esta enfermedad está estrechamente relacionada con el HLA, puede ocurrir en su ausencia 36,[41][42][43] .…”
Section: Patogénesisunclassified
“…La distribución geográfica de este alelo puede explicar por qué el prurigo actínico es más común en algunos lugares de Norteamérica, Centroamérica y Suramérica. Aunque esta enfermedad está estrechamente relacionada con el HLA, puede ocurrir en su ausencia 36,[41][42][43] .…”
Section: Patogénesisunclassified
“…Multiple studies have reported the association of human leukocyte antigen (HLA) genes with susceptibility to develop AP and shown ethnic differences. There are known associations with class II HLA alleles, in particular HLA‐DRB1*04:07 in the British and Mexicans , DR3 in South American and DRB1*14 in Canadian populations . Associations with class I HLA alleles such as HLA‐Cw*04, A*24, A*28 and B*39 have also been reported .…”
Section: Introductionmentioning
confidence: 99%
“…In the Caucasian population, AP is generally of childhood onset, with female predominance . This condition is found more frequently in Native American (Amerindian), the Mestizo population and some Indian groups from Mexico, Guatemala, Honduras, Colombia, Bolivia and Peru, as well as in some populations from Northwestern Europe (England, Ireland and Scotland) .…”
Section: Introductionmentioning
confidence: 99%
“…But despite this, dermatologists share so many common objectives, and approaches used on one side of the world may well have value and be adopted on the other. So techniques used to educate patients in Europe, North America and Australasia about the consequences of sun exposure and protection from the sun and skin cancer are very similar to those that should be employed in preventing African patients with albinism from early‐onset nonmelanoma skin cancer, or native Americans from suffering the consequences of inherited photodermatitis . We may also be able to learn by simple measures, used in the poorest of communities, that are relevant to the needs of our own patients.…”
mentioning
confidence: 99%